2021
DOI: 10.1002/chem.202001356
|View full text |Cite
|
Sign up to set email alerts
|

Iridoid Sex Pheromone Biosynthesis in Aphids Mimics Iridoid‐Producing Plants

Abstract: Biosynthesis of (1R,4aS,7S,7aR)-nepetalactol (1) and (4aS,7S,7aR)-nepetalactone (2) in plants involves iridoid synthase (ISY), an atypical reductive cyclase that catalyses the reduction of 8-oxogeranial into the reactive enol of (S)-8-oxocitronellal, and cyclization of this enol intermediate, either non-enzymatically or by a nepetalactol-related short chain dehydrogenase enzyme (NEPS) that yields the nepetalactols. In this study, we investigated the biosynthesis in vivo of 1 and 2 in the pea aphid, Acyrthosiph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Here we elucidated the entire iridoid pathway in the pea aphid A. pisum . Previously reported feeding studies in pea aphids (21), as well as the spatial localization of nepetalactone biosynthesis (20), guided the identification of the six biosynthetic genes (Figure 1A). The characterization of these enzymes indicates that the plant and aphid nepetalactone biosynthetic pathways are composed of the same chemical transformations.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Here we elucidated the entire iridoid pathway in the pea aphid A. pisum . Previously reported feeding studies in pea aphids (21), as well as the spatial localization of nepetalactone biosynthesis (20), guided the identification of the six biosynthetic genes (Figure 1A). The characterization of these enzymes indicates that the plant and aphid nepetalactone biosynthetic pathways are composed of the same chemical transformations.…”
Section: Discussionmentioning
confidence: 87%
“…Notably, among these transcripts were eight genes encoding the entire mevalonate pathway starting from acetyl-CoA to IPP and DMAPP (Figure 1B). Previously reported isotopic labeling studies indicated that the iridoid pathways in pea aphids and plants share at least some of the same biosynthetic intermediates (21). We therefore assumed that the biochemical transformations in pea aphids were the same as those established in Nepeta .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the biosynthetic pathways to nepetalactone in both Nepeta spp. (Lichman et al, 2019(Lichman et al, , 2020 and aphids (K€ ollner et al, 2022;Partridge et al, 2021) have been elucidated. In a remarkable example of convergent evolution, the chemical steps are identical but the enzymes are of distinct origins.…”
Section: Introductionmentioning
confidence: 99%
“…The iridoid pathway involves the catalysis of geranyl diphosphate by geranyl diphosphate diphosphatase (GES) to produce geraniol [ 5 ]. Subsequently, geraniol is catalyzed by geraniol 10-hydroxylase (G8H) and 8-hydroxygeraniol dehydrogenase (8HGO) to form 10-Oxogeranial [ 6 , 7 ]. The catalysis of 10-Oxogeranial involves iridodial synthase (IS) and iridodial oxidoreductase (IO), resulting in the formation of 7-Deoxyloganetic acid [ 8 ].…”
Section: Introductionmentioning
confidence: 99%